Emerging Infectious Agents and Blood Safety in Latin America - Levi, José Eduardo (Frontiers in Medicine, 2018)
Historically, emerging infectious agents have been an important driving force towards the enhancement of blood safety, illustrated by the sharp reduction in the transmission of infectious agents by blood transfusion after human immunodeficiency virus (HIV) epidemics. In general, Latin American countries have introduced screening for microorganisms with proven blood transmission with some delay in comparison to developed countries, but, nowadays, all Latin American countries comply with a minimum standard of screening which includes Hepatitis B, C, HIV, Treponema pallidum and Trypanosoma cruzi. Noticeably, all those agents, in addition to HTLV, cause chronic infections. In contrast, in the last decade, the region has witnessed explosive outbreaks of arboviral diseases, representing a new challenge to the blood system, threatening not only blood safety but also availability. So far, the clinical impact of transfusion-transmitted Dengue, Chikungunya or Zika has not been evident, precluding immediate reaction from the authorities. A number of other arboviruses are endemic in the region and may, unpredictably, originate new epidemics. Several measures must be taken in preparedness for the potential emergence of another arbodisease.